Student’s perception towards online shopping that affects buying behavior / Nuradella Aira Hamdan - Hamdan, Nuradella Air (2016)
University is a place where students seeks knowledge and learn how to be socialized with everyone around them and get involved with campus activities. For normal students, they are using internet as a daily basis in order to complete their daily task such as assignments and all. In order to get information to complete their assignments they need the internet to do some searching. Internet also is a medium for students to communicate among other students even lecturers. Accordingly, Internet access in schools has increased greatly over the last 20 years (Berson, 2000).